2019
DOI: 10.14309/ajg.0000000000000295
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Postprandial Regurgitation vs Rumination in Patients With Refractory Gastroesophageal Reflux Disease Symptoms: Identification of a Distinct Rumination Pattern Using Ambulatory Impedance-pH Monitoring

Abstract: OBJECTIVES: Up to 20% of patients with refractory gastroesophageal reflux disease (GERD) might have postprandial rumination. The aim of this study was to distinguish persistent GERD-related postprandial regurgitation from rumination in patients with refractory GERD undergoing ambulatory multichannel intraluminal impedance–pH (MII-pH) monitoring. METHODS: We first characterized 24-hour and postprandial MII-pH patterns in 28 consecutive patients with conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 36 publications
1
35
0
4
Order By: Relevance
“…We analyzed the MII-pH tracings using the dedicated softwares (Diversatek Healthcare or Jinshan Science and Technology) and visual editing based on our standard protocol. 1,19,20 Mean nocturnal baseline impedance…”
Section: Multichannel Intraluminal Impedance Ph-monitoring Protocolmentioning
confidence: 99%
“…We analyzed the MII-pH tracings using the dedicated softwares (Diversatek Healthcare or Jinshan Science and Technology) and visual editing based on our standard protocol. 1,19,20 Mean nocturnal baseline impedance…”
Section: Multichannel Intraluminal Impedance Ph-monitoring Protocolmentioning
confidence: 99%
“…The number of rumination episodes was reported by patients (not by objective testing). In our previous report, 37 24‐hour impedance pH‐metry showed that patients with RS reported their symptoms quite accurately. This study aimed to understand pathophysiological mechanisms in patients with rumination but does not include long term evaluation of the effect of DiaB treatment on vagal tone and rumination events.…”
Section: Discussionmentioning
confidence: 89%
“…14,15,17,32,33 The number of rumination episodes was reported by patients (not by objective testing). In our previous report, 37 24-hour impedance pH-metry showed that patients with RS reported their symptoms…”
Section: Discussionmentioning
confidence: 89%
“…Yadlapati et al 31 reported that the number of nonacid reflux events on PPI was significantly associated with the frequency of rumination episodes. A more recent study using MII-pH off PPI therapy 41 suggested that rumination patients had normal AET in the esophagus but significantly higher numbers of upright nonacid reflux episodes with high proximal extent compared with refractory GERD patients (Fig. 1B).…”
Section: Evaluation Of Rumination Syndrome and Supragastric Belching mentioning
confidence: 89%